Forefoot width correction in patients with hallux valgus after rotational scarf osteotomy - Mombello Zuleta, Franco; Butteri, Ana Ines; Chaparro Ravazzano, Felipe; Pellegrini Pucci, Manuel; Carcuro Urresti, Giovanni; Ortiz Mateluna, Cristian (Journal of the Foot & Ankle, 2022)
Objective: Our objective was to compare foot width (bony and soft tissues) in radiological images pre- vs. post-corrective scarf osteotomy in patients with hallux valgus. Methods: We retrospectively performed measurements of forefoot width (both bony diameter and total diameter including soft tissues) on anterior posterior standard radiographs of 30 patients, totaling 42 feet, pre- and postoperatively, at three months. These measurements were performed by two evaluators and their reliability was calculated. Results: Radiologically, preoperative mean of the 1-5 metatarsal bony width was 89.30mm (SD ± 5.8), reduced to 80.42mm postoperatively (SD ± 3.5; p<0.001). Regarding the soft tissue width, preoperative mean was 102.45mm (SD ± 6.4) and postoperative, 98.3mm (SD ± 5.1; p<0.001). The interclass correlation coefficient between both observers was excellent in most measurements (range, 0.884-0.973). Conclusion: We report an objective reduction in forefoot width, in both bony and soft tissue diameter, finding means of 8.88 mm (10%) and 4.12mm (4.1%), respectively, after scarf-Akin osteotomy. Level of Evidence IV; Case Series.